Improving Students Activity and Students Learning Outcomes by Using Realistic Mathematic Learning - Dewi Fatoni (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2020)
The purpose of the research to describe the students activities during the application of realistic mathematic and to describe the students learning outcomes during the application of realistic mathematic. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VII at SMP Negeri 2 Grujugan Bondowoso. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and student learning outcomes.Keywords: PMR, students activity, and learning outcome